ANALISIS PENGARUH PENERAPAN GREEN PRACTICE TERHADAP KEPUTUSAN BERKUNJUNG DI SHANTI KITCHEN & COFFEE, JAKARTA - Rosalia Indah Br Sitepu; Vishnuvardhana S. Soeprapto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growing awareness of environmental issues has driven the restaurant industry to adopt environmentally friendly practices, commonly referred to as green practice, as part of a sustainable operational strategy. This study aims to analyze the influence of green practice implementation—comprising the dimensions of green action, green food, and green donation—on consumer visit decisions at Shanti Kitchen & Coffee, Jakarta. This study employs a quantitative approach with a descriptive and associative research design. Data were collected through a structured questionnaire distributed to 90 respondents selected via accidental sampling from a population of 800 visitors to Shanti Kitchen & Coffee during the period of January to December 2025. The research instrument was developed using a four-point Likert scale. Multiple linear regression analysis was applied using SPSS version 25, encompassing validity and reliability tests, classical assumption tests, and hypothesis testing through t-test, F-test, and coefficient of determination. The findings indicate that, partially, only the green food dimension exerts a significant influence on visit decisions (t-value 3.374 sig 0.001 < 0.05), while green action (sig 0.056) and green donation (sig 0.519) do not demonstrate significant partial effects. Simultaneously, the green practice variable as a whole significantly influences visit decisions (F-value 9.82 sig 0.000 < 0.05). The Adjusted R Square value of 0.229 indicates that green practice explains 22.9% of the variation in visit decisions, with the remaining 77.1% attributed to factors outside the scope of this study. This study offers practical implications for the restaurant industry, particularly in optimizing green food as the most influential factor in consumer visit decisions. Restaurants are advised to strengthen communication regarding the use of organic and locally sourced ingredients, enhance the visibility of green action practices, and broaden green donation programs through active consumer engagement. Future research is encouraged to expand the scope of variables and study objects to yield more comprehensive findings.